Low Cost Optical-electronic Sensor Development Based on Raman Spectroscopy for Liquid - Luqman Aji Kusumo; Totok Mujiono; Hendra Kusuma (Department of Electrical Engineering ITS and FORTEI, 2020)
Spectroscopy is a method that used to identifychemical structure of substances using its spectral patterncharacteristics. Optical spectroscopy term can be applied to anykind of optical photon interactions with matter. Ramanspectroscopy essentially shows spectral response like thewavelength of scattered light is shifted regarding initializingexcitation wavelength. In this paper, we propose a design of lowcost optical-electronic sensor based on Raman spectroscopy.This low cost optical-electronic sensor employs a violet-blue 405nm wavelength laser diode, a biconvex lens with 5 cm diameterand focus point, a test tube, and a Complementary Metal OxideSemiconductor (CMOS) sensor. We tested this low cost opticalelectronic sensor based on Raman spectroscopy in darkcondition. Combination of these hardware and components canprovide measurement result to any liquid sample. From thisexperiment, even all liquid samples that used to test thiscombination of hardware and components are transparent, theystill have different Raman spectra. This combination ofhardware and components can be implemented into someapplication for instance body liquid measurement such as blood.In specific application, we need to employ data analysis and abunch of data set which are organized into three different groupsuch as training data, validation data, and test data group,combined with this developed instrumentation.Keywords: CMOS sensor, laser diode, Raman scattering, Raman spectroscopy, spectroscope.